The Relationship between Autism Spectrum Disorder and Tourette Syndrome in Childhood: An Overview of Shared Characteristics - Rizzo, Renata; Gulisano, Mariangela; Domini, Carla Noemi; Ferro, Maria Cristina; Curatolo, Paolo (Journal of Pediatric Neurology, 2017)
Autism spectrum disorder (ASD) and Tourette syndrome (TS) are neurodevelopmental disorders. ASD and TS are traditionally considered to be separate conditions. Nevertheless, these disorders have a high degree of overlap, and “pure” cases are rare in both clinical and population-based studies. The aim of the present review was to analyze the similarities and differences between ASD and TS on the basis of genetic and neuroradiological findings.
Keywords: Autism spectrum disorder; Tourette syndrome; comorbidity; genetics